Suppression of starch synthase I expression affects the granule morphology and granule size and fine structure of starch in wheat endosperm - McMaugh, Stephen J (Journal of experimental botany, 2014)
Studies in Arabidopsis and rice suggest that manipulation of starch synthase I (SSI) expression in wheat may lead to the production of wheat grains with novel starch structure and properties. This work describes the suppression of SSI expression in wheat grains using RNAi technology, which leads to a low level of enzymatic activity for SSI in the developing endosperm, and a low abundance of SSI protein inside the starch granules of mature grains. The amylopectin fraction of starch from the SSI suppressed lines showed an increased frequency of very short chains (degree of polymerization, dp 6 and 7), a lower proportion of short chains (dp 8-12), and more intermediate chains (dp 13-20) than in the grain from their negative segregant lines. In the most severely affected line, amylose content was significantly increased, the morphology of starch granules was changed, and the proportion of B starch granules was significantly reduced. The change of the fine structure of the starch in the SSI-RNAi suppression lines alters the gelatinization temperature, swelling power, and viscosity of the starch. This work demonstrates that the roles of SSI in the determination of starch structure and properties are similar among different cereals and Arabidopsis